Criminal profiling: an introduction to behavioral evidence analysis - Turvey, Brent E. (Elsevier, Academic Press, 2023)
"Criminal Profiling: An Introduction to Behavioral Evidence Analysis, Fifth Edition, maintains the same core foundation that made previous editions best sellers in the professional and academic community worldwide. Written for practicing behavioral analysts and aspiring students alike, this work emphasizes an honest understanding of crime and criminals. Newly updated, mechanisms for the examination and classification of both victim and offender behavior have been improved. In addition to refined approaches toward international perspectives, chapters on psychological autopsies, scene investigation reconstruction, court issues and racial profiling have also been added."--